Bioceramics in modern endodontics - A. V. Mitronin; D. A. Ostanina; Yu. A. Mitronin (Эндодонтия Today)
The introduction of modified bioceramic calcium silicate- based materials into clinical practice has changed the standards and strategies of endodontic treatment. The review article highlights modern calcium silicate- based cements that are used in various areas of endodontics, including vital pulp therapy, root canal obturation, management of endodontic complications and pulp regeneration. The classifications of bioceramic materials based on their chemistry and specific use in endodontics are presented. The physicochemical and biological properties of various types of materials, as well as the features of their clinical application, are described.